2022
DOI: 10.1093/eurpub/ckac125
|View full text |Cite
|
Sign up to set email alerts
|

The French Covid-19 vaccination policy did not solve vaccination inequities: a nationwide study on 64.5 million people

Abstract: Background To encourage Covid-19 vaccination, France introduced during the Summer 2021 a ‘Sanitary Pass’, which morphed into a ‘Vaccine Pass’ in early 2022. While the sanitary pass led to an increase in Covid-19 vaccination rates, spatial heterogeneities in vaccination rates remained. To identify potential determinants of these heterogeneities and evaluate the French sanitary and vaccine passes’ efficacies in reducing them, we used a data-driven approach on exhaustive nationwide data, gatheri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
7
1
Order By: Relevance
“…In general terms, our results are consistent with previous literature, indicating that vaccine coverage is lower in vulnerable populations living in poverty, having lower literacy and with a lesser educational level. 13,26,40 Despite the fact that our results show a statistically significant correlation between the vulnerability of different municipalities and the COVID-19 vaccination coverage-i.e. municipalities with lower SES exhibit lower coverage-, different school types exhibit distinct vaccination coverage.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…In general terms, our results are consistent with previous literature, indicating that vaccine coverage is lower in vulnerable populations living in poverty, having lower literacy and with a lesser educational level. 13,26,40 Despite the fact that our results show a statistically significant correlation between the vulnerability of different municipalities and the COVID-19 vaccination coverage-i.e. municipalities with lower SES exhibit lower coverage-, different school types exhibit distinct vaccination coverage.…”
Section: Discussioncontrasting
confidence: 77%
“…In general terms, our results are consistent with previous literature, indicating that vaccine coverage is lower in vulnerable populations living in poverty, having lower literacy and with a lesser educational level. 13, 26, 40…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to COVID-19, concerns have been raised that unequal access to vaccination may exacerbate previous health disparities. Studies conducted in different contexts, mostly in high-income countries, have identified that populations in positions of greater social vulnerability, as well as residents in regions with worse socioeconomic indicators, have lower vaccination coverage [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%